Riscos na reutilização de produtos médicos esterilizados em óxido de etileno - Sundin, Mônica Saladini (2014)
The present study analyzed 275 results for residues of ethylene oxide (ETO) and by-products such as ethylene glycol (ETG) and ethylene chloridrine (ETCH), in medical devices sterilized using ethylene oxide. The methodology differs from other studies for not being a simulation, but rather real cases of sterilized devices in which the amount of residue was measured. The quantities of residues obtained were compared with the top levels established by regulations. There was a great adjustment of the results to the limits established by the regulation. However problems were found mainly in the large amount of outliers values, a problem that indicates possible issues during the airing stage of the devices. In order to support this study, related studies have been made and are presented here with the names: Analysis of Uncertainty in Chromatograph Calibration Curves in Ethylene Oxide Residues Measuring; Ethylene Oxide Residuals in Gelfoam® and Ethylene Oxide Residuals in Saline Bottles.